PEMBERIAN MAKANAN TAMBAHAN BAGI IBU HAMIL DENGAN KEK DI DESA SUMPUR JAYA KECAMATAN KETAMBE - Hasanalita, Hasanalita (PUSAT PENELITIAN DAN PENGABDIAN PADA MASYARAKAT (PPPM) POLITEKNIK NEGERI SAMBAS, 2023)
The problem of nutritional disorders in pregnant women is a problem that needs to be addressed seriously. Pregnant women with Chronic Energy Deficiency (KEK) can have an impact on the growth and health of their babies. Deficiency of macro and micro nutrients in pregnant women and children has an impact on the quality of life. Riskesdas data shows that the percentage of pregnant women who experience CED is 17.3% of all pregnant women in Indonesia. Most pregnant women who experience CED are aged 15-19 years. Data on the prevalence of pregnant women experiencing CED in Aceh province is 24.2%. The aim: of this community service is to provide education about providing additional food through empowering cadres and pregnant women who experience CED. Methods: advocacy (discussions were held with relevant village officials and cadres), atmosphere building method (providing health education and preparing health promotion media), community movement method (empowering health cadres). Results the program was implemented smoothly, the enthusiasm of the participants (mothers) was visible. mothers and cadres) who are high. This can provide support for government programs in efforts to increase mothers' awareness and knowledge about providing additional food through empowering cadres. And government efforts in nutritional education programs in providing additional food. Evaluation of the PMT program is that the distribution of PMT is not optimal, there is a lack of awareness among pregnant women to carry out health checks and additional food is not consumed by pregnant women. Conclusion through this outreach, mothers and cadres can gain useful knowledge about providing additional food.